PUPSI :uma proposta de processo unificado para políticas de segurança da informação - Anjos, Ivano Miranda dos (2004)
The way to deal with information assets means nowadays the main factor not only for the success but also for keeping the companies in the global world. The number of information security incidents has grown for the last years. The establishment of information security policies that search to keep the security requirements of assets in the desired degrees is the major priority for the companies. This dissertation suggests a unified process for elaboration, maintenance and development of information security policies, the Processo Unificado para Políticas de Segurança da Informação - PUPSI. The elaboration of this proposal started with the construction of a structure of knowledge based on documents and official rules, published in the last two decades, about security policies and information security. It's a model based on the examined documents which defines the needed security policies to be established in the organization, its work flow and identifies the sequence of hierarchy among them. It's also made a model of the entities participating in the process. Being the problem treated by the model so complex, which involves all security policies that the company must have. PUPSI has an interative and developing approach. This approach was obtained from the instantiation of the RUP - Rational Unified Process model. RUP is a platform for software development object oriented, of Rational Software (IBM group). Which uses the best practice known by the market. PUPSI got from RUP a structure of process that offers functionality, diffusion capacity and comprehension, performance and agility for the process adjustment, offering yet capacity of adjustment to technological and structural charges of the market and the company